A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Prioritizing taxa for genetic reference database development to advance inland water conservation - Marie-Eve Monchamp; Zofia E. Taranu; Rebecca E. Garner; Tessa Rehill; Olivier Morissette; Lars L. Iversen; Vincent Fugère; Joanne E. Littlefair; Naíla Barbosa da Costa; Jessica E. Desforges; Joe R. Sánchez Schacht; Alison M. Derry; et al. (Biological Conservation, 2023)

Genetic variation and clonal diversity in floating aquatic plants: Comparative genomic analysis of water hyacinth species in their native range - Nicolay Leme da Cunha; Haoran Xue; Stephen I. Wright; Spencer C. H. Barrett (Molecular Ecology, 2022)
Many eukaryotic organisms reproduce by sexual and asexual reproduction. Genetic diversity in populations can be strongly dependent on the relative importance of these two reproductive modes. Here, we compare the amounts and patterns of genetic diversity in related water hyacinths that differ in their propensity for clonal propagation – highly clonal Eichhornia crassipes and moderately clonal E. azurea (Pontederiaceae). Our comparisons involved genotype‐by‐sequencing (GBS) of 137 E. crassipes ramets from 60 locations (193,495 nucleotide sites) and 118 E. azurea ramets from 53 locations (198,343 nucleotide sites) among six hydrological basins in central South America, the native range of both species. We predicted that because of more prolific clonal propagation, E. crassipes would exhibit lower clonal diversity than E. azurea . This prediction was supported by all measures of clonal diversity that we examined. Eichhornia crassipes also had a larger excess of heterozygotes at variant sites, another signature of clonality. However, genome‐wide heterozygosity was not significantly different between the species. Eichhornia crassipes had weaker spatial genetic structure and lower levels of differentiation among hydrological basins than E. azurea , probably because of higher clonality and more extensive dispersal of its free‐floating life form. Our findings for E. crassipes contrast with earlier studies from the invasive range which have reported very low levels of clonal diversity and extensive geographic areas of genetic uniformity.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Resistance, resilience, and functional redundancy of freshwater bacterioplankton communities facing a gradient of agricultural stressors in a mesocosm experiment - Naíla Barbosa da Costa; Vincent Fugère; Marie‐Pier Hébert; Charles C.Y. Xu; Rowan D.H. Barrett; Beatrix E. Beisner; Graham Bell; Viviane Yargeau; Gregor F. Fussmann; Andrew Gonzalez; B. Jesse Shapiro (Molecular Ecology, 2021)
Agricultural pollution with fertilizers and pesticides is a common disturbance to freshwater biodiversity. Bacterioplankton communities are at the base of aquatic food webs, but their responses to these potentially interacting stressors are rarely explored. To test the extent of resistance and resilience in bacterioplankton communities faced with agricultural stressors, we exposed freshwater mesocosms to single and combined gradients of two commonly used pesticides: the herbicide glyphosate (0–15 mg/L) and the neonicotinoid insecticide imidacloprid (0–60 μg/L), in high or low nutrient backgrounds. Over the 43‐day experiment, we tracked variation in bacterial density with flow cytometry, carbon substrate use with Biolog EcoPlates, and taxonomic diversity and composition with environmental 16S rRNA gene amplicon sequencing. We show that only glyphosate (at the highest dose, 15 mg/L), but not imidacloprid, nutrients, or their interactions measurably changed community structure, favouring members of the Proteobacteria including the genus Agrobacterium . However, no change in carbon substrate use was detected throughout, suggesting functional redundancy despite taxonomic changes. We further show that communities are resilient at broad, but not fine taxonomic levels: 24 days after glyphosate application the precise amplicon sequence variants do not return, and tend to be replaced by phylogenetically close taxa. We conclude that high doses of glyphosate – but still within commonly acceptable regulatory guidelines – alter freshwater bacterioplankton by favouring a subset of higher taxonomic units (i.e., genus to phylum) that transiently thrive in the presence of glyphosate. Longer‐term impacts of glyphosate at finer taxonomic resolution merit further investigation.

Invasion genetics of Senecio vulgaris: loss of genetic diversity characterizes the invasion of a selfing annual, despite multiple introductions - Bi-Ru Zhu; Spencer C. H. Barrett; Da-Yong Zhang; Wan-Jin Liao (Biological Invasions, 2017)

Genetic uniformity characterizes the invasive spread of water hyacinth ( Eichhornia crassipes ), a clonal aquatic plant - YUAN-YE ZHANG; DA-YONG ZHANG; SPENCER C. H. BARRETT (Molecular Ecology, 2010)